Dynamic modeling of lactate in ischemia for high performance athletes - Leminszka, M A; Dieck Assad, G; Martínez, S O; Garza, J E (Revista Mexicana de Ingenieria Biomedica, 2018)
The following article proposes a dynamic model to measure lactic acid for high performance athletes in ischaemia, in other words, when there is a blood flow reduction (source of oxygen). An introduction to the lactate regulation in ischaemia is presented to describe the parameters involved in the dynamic modeling. The results indicate that the dynamic model predicts effectively the amount of lactate in physical tests performed to three athletes. When comparing the model results with samples of blood measurements from an electronic analyzer, the dynamic model obtains an maximum efficiency (accuracy) of 96.46% having an error range between 3.5% to 11.8%. Those results improve the predictions from an ideal model, where an efficiency of 90.61% is obtained. The efficiencies are indicative of how close the model can be to measurements performed by an electronic blood sample analyzer device.